THE BUTTERFLY FAUNA OF PU HOAT NATURE RESERVE, NGHE AN PROVINCE - Van Bac, Bui (Journal of Forestry Science and Technology, 2021)
Pu Hoat Nature Reserve (NR) is the part of the Western Nghe An Biosphere Reserve (Nghe An province, central Vietnam), and identified as an important area for biodiversity conservation in the North Central Coastal Vietnam. This nature reserve hosts various ecosystems and landscapes with four main formations including closed forests, sparse forests, scrubs and grass vegetation. It is well known that butterflies with their high diversity and abundance are one of the most important players in many ecosystem processes. The loss of butterfly diversity may lead to negative cascading effects across whole communities. Therefore, conservationists have often taken the advantage of butterfly diversity as an indicator for forest planning and management in the tropics. Between April and December 2020, we sampled butterflies over three consecutive collection trips throughout Pu Hoat NR. In total, 155 butterfly taxa were recorded during the dedicated surveys of this study, in addition to 12 species-level records from previous studies. The main aim of this paper is to give a first report of all butterfly species known to date in Pu Hoat NR. Additionally, the study identified butterfly species as potential bio-indicator species for different forest types in Pu Hoat NR. This information may be useful for monitoring biodiversity in Vietnam forests where have witnessed the high relative rate of habitat loss and degradation.